Predictors of preventive practices towards hand-foot-and-mouth disease among mothers of preschool children using socioecological model in Klang district - Suliman, Qudsiah (2017)
Background: The epidemics of Hand-foot-and-mouth Disease (HFMD) has recurred globally, causing significant morbidity and mortality. During which Klang District, Selangor was among 3 governance districts with the most cases of HFMD in Malaysia by August 2016, update on local assessment of Socioecological Model predictors of preventive practices towards HFMD is fundamental.